Drama as The Way To Integrate Literature in English Language Teaching - Tiara Nadiya Itabi Wahya; Muhammad Iqbal Amrullah; Wahyu Indah Mala Rohmana (University of Darussalam Gontor, 2023)
This article analyzes how drama in learning English can be an interesting and not boring lesson for students at school. This is to ensure that learning English is well integrated. Drama can be used to teach English skills, speaking, and listening. In addition, the teacher hopes that learning drama can be a way to improve learning literature in schools and increase students' talents. This study was conducted at the Al-Mahduqiah Modern Islamic Boarding School in East Java that uses a curriculum muallimin. The research methodology used in this article is qualitative, using a literature survey and interviews. As a basis for the analysis, interviews were conducted with two teachers. The purpose of studying literature learning is to find out how English is used in the process of teaching. The results of this study revealed that drama can improve the integration of literature learning in the classroom. Moreover, drama can be used as a means to engage students more enthusiastically in learning English and make it a more effective medium for teaching English.